Formulation engineering for optimizing ternary electron acceptors exemplified by isomeric PC71BM in planar perovskite solar cells. Issue 48 (27th October 2016) - Dai, Si-Min; Zhang, Xin; Chen, Wei-Yi; Li, Xiang; Tan, Zhan'ao; Li, Cong; Deng, Lin-Long; Zhan, Xin-Xing; Lin, Min-Song; Xing, Zhou; Wen, Tao; Ho, Rong-Ming; et al.
Abstract : PC71 BM was isolated into three typically synthesizable isomers for a formulation engineering to make the most efficient electron acceptor with best formulation of the regioisomers/stereoisomers. Abstract : As the most prevalently used fullerene-based electron acceptor in organic–inorganic solar cells, [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM) was isolated into three typical isomers of α-, β1 - and β2 -PC71 BM with comparable molecular orbital energy levels for exemplifying a formulation engineering based on blending the three isomers to improve photovoltaic performance. The power conversion efficiency (PCE), photocurrent hysteresis and stability of planar heterojunction perovskite (CH3 NH3 PbI3 ) solar cells have been optimized by formulation engineering with mixed PC71 BM (α : β1  : β2 = 17 : 1 : 2), the specific mixture which represents the best electron acceptor superior to either each of the purified isomers or any other ternary isomers of PC71 BM. Microscopic analyses support that molecular aggregation of the isomeric PC71 BM was critical to influence the surface morphology and, in turn, the PCE in the range of 0.38–17.56% of the perovskite solar cells involved. This finding about isomer-dependent photovoltaic performance launches a heretofore unknown strategy of formulation engineering for making efficient electron acceptors by mixing various fullerene derivatives having isomeric structures or beyond.